ROMANIAN AS A SECOND LANGUAGE (RL2). PORTRAITS OF THE RL2 USER - VASIU, Lavinia; BOCOȘ, Cristina; MARDALE, Alexandru (Studia Universitatis Babeș-Bolyai Philologia, 2025)
Fortunately, in recent decades, there has been a growing interest in research papers focused on speakers of Romanian as a second/as a foreign language (RL2): individuals who reside in Romania for shorter or longer periods (foreign students, various professional categories employed for fixed terms, immigrants, etc.); pupils or students belonging to communities where Romanian is learned/spoken only at school, during Romanian language classes (as a second language); individuals who, for various reasons, learn Romanian as a second language outside Romania (for example, students in philology departments at universities abroad); or even, marginally included, people (generally young) who speak Romanian as a heritage language.